2015
DOI: 10.1038/onc.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of estrogen independence induces TOB1-related mechanisms supporting breast cancer cell proliferation

Abstract: Resistance to therapies targeting the estrogen pathway remains a challenge in the treatment of estrogen-receptor positive breast cancer. To address this challenge, a systems biology approach was used. A library of siRNAs targeting an estrogen receptor- and aromatase-centered network identified 46 genes that are dispensable in estrogen-dependent MCF7 cells, but are selectively required for the survival of estrogen-independent MCF7-derived cells, and multiple additional estrogen-independent breast cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
1
27
1
Order By: Relevance
“…Our study found that knockdown of TOB1 enhanced the proliferative activity of MSCs, which is consistent with results in mouse embryonic stem cells [26]. However, a recent study found that TOB1 knockdown inhibited growth of estrogen-independent estrogen receptor positive breast cancer cells [27]. The reported variability in TOB1 function may be due to distinctive regulation of survival and cell cycle signaling in different cell types.…”
Section: Discussionsupporting
confidence: 81%
“…Our study found that knockdown of TOB1 enhanced the proliferative activity of MSCs, which is consistent with results in mouse embryonic stem cells [26]. However, a recent study found that TOB1 knockdown inhibited growth of estrogen-independent estrogen receptor positive breast cancer cells [27]. The reported variability in TOB1 function may be due to distinctive regulation of survival and cell cycle signaling in different cell types.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, it is unclear how well WGCNA performs under small sample size restrictions. To explore the mechanisms of resistance to therapies targeting estrogen pathways in the treatment of estrogen receptor (ER) positive breast cancer, we previously performed a systemic biological screening of a library of siRNAs targeting an ER- and aromatase-centered network [15]. We identified 46 genes that are dispensable in the estrogen-dependent MCF7 cell lines, but are selectively required for the survival of estrogen-independent MCF7-derived cell lines (LCC1 and LCC9).…”
Section: Introductionmentioning
confidence: 99%
“…SiRNAs against those genes were distributed into 11 x 96-well plates. Two siRNAs were selected for each gene and mixed in one well (Zhang et al ., 2016). The advantage of our method provides high-throughput screening by using automatic machines (Cybio, Combi-nL or Wellmate dispenser) to dispense liquid to speed the screening process.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of cancer cell lines had been used in RNAi screening with our methods (Astsaturov et al ., 2010; Murray et al ., 2014; Zhang et al ., 2016), such as estrogen positive breast cancer MCF7, estrogen-independent MCF7 (LCC1 and LCC9), triple negative breast cancer MDA-MB-231, epidermoid cancer A431 and human fibroblast HFF1 cells etc . For each cell line, the optimal transfection reagent has to be determined before RNAi library screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation